Least Absolute Shrinkage and Selection Operator (LASSO) untuk Mengatasi Multikolinearitas pada Model Regresi Linear Berganda - Annisa Juwita Mahalani; Nur Azizah Komara Rifai (Bandung Conference Series: Statistics, 2022)
Abstract. Linear regression analysis is one of them used to see the intersection between non-free variables and free variables. If there is more than one free variable, multiple linear regression analysis is used. Regression models are said to be good if the assumptions are met. One of them is the absence of multicollinearity, namely a high correlation or relationship between independent variables. In the event of multicholinearity, it can be resolved using the Least Absolute Shrinkage And Selection Operator (LASSO) regression method. The LASSO regression method was first introduced by Robert Tibshirani in 1996. This method can select variables and overcome multicholinearity. To make it easier to computate LASSO, you can use the Least Angle Regression (LARS) algorithm. In this study, we will discuss the application of the LASSO regression method to data on the number of poor people in Indonesia in 2020. By looking at the correlation coefficient and VIF values, there are 3 variables that indicate multicollinearity problems. The gross regional domestic product variable is the variable that is first entered in the model, meaning that the variable is most correlated with error. Abstrak. Analisis regresi linear salah satunya digunakan untuk melihat perngaruh antara variabel tak bebas dengan variabel bebas. Apabila variabel bebas lebih dari satu maka digunakan analisis regresi linear berganda. Model regresi dikatakan baik apabila asumsinya terpenuhi. Salah satunya adalah tidak adanya multikolinearitas yaitu korelasi atau hubungan yang tinggi diantara variabel bebas. Apabila terjadi multikolinearitas, dapat diatasi dengan menggunakan metode regresi Least Absolute Shrinkage And Selection Operator (LASSO). Metode regresi LASSO diperkenalkan pertama kali oleh Robert Tibshirani pada tahun 1996. Metode ini dapat menyeleksi variabel dan mengatasi multikolinearitas. Untuk mempermudah komputasi LASSO, dapat menggunakan algoritma Least Angle Regression (LARS). Dalam penelitian ini, akan dibahas penerapan metode regresi LASSO pada data jumlah penduduk miskin di Indonesia tahun 2020. Dengan melihat nilai koefisien korelasi dan nilai VIF, terdapat 3 variabel yang terindikasi masalah multikolinearitas. Variabel produk domestik regional bruto adalah variabel yang pertama kali masuk pada model artinya variabel tersebut paling berkorelasi dengan galat.